Positive role of 1-aminocyclopropane-1-carboxylate deaminase-producing endophytic Streptomyces sp. GMKU 336 on flooding resistance of mung bean - Jaemsaeng, Ratchaniwan; Jantasuriyarat, Chatchawan; Thamchaipenet, Arinthip (Agriculture and Natural Resources, 2018)
Previously, a plant growth-promoting endophytic Streptomyces sp., namely GMKU 336, has been shown to improve salt tolerance in rice through the action of 1-aminocyclopropane-1-carboxylate deaminase (ACCD) by converting a precursor of ethylene, (ACC) in plants into ammonia and α-ketobutyrate and consequently reducing the ethylene level. In this study, strain GMKU 336 and its ACCD-deficient mutant were further investigated regarding flooding tolerance in mung bean CN72 [Vigna radiata (L.) Wilczek cv.CN72]. The results clearly demonstrated that mung bean associated with Streptomyces sp. GMKU 336 significantly increased plant elongation and biomass, chlorophyll content, leaf area, leaf color and adventitious roots, and reduced the ethylene level under flooding conditions when compared to uninoculated plants and those inoculated with the ACCD-deficient mutant. It was concluded that ACCD producing Streptomyces sp. GMKU 336 that beneficially improved salt tolerance in rice also enhanced flooding tolerance in mung bean via the action of ACCD.